The Impact of Covid-19 on Supply Chain Management and Global Economy Development - E. S. Derevyankina; D. G. Yankovskaya (International Journal of Supply Chain Management, 2020)
Abstract—The impact of COVID-19 on our inter-connected economies and businesses has been significant, putting supply chains around the world under unprecedented pressure and severely disrupting global trade. Social distancing adopted by the governments in most countries of the world to contain the outbreak of the virus has many implications for the financial reporting of economic entities. The aim of the article is to consider the potential consequences of coronavirus for the presentation and disclosure of information in financial statements by economic entities. Emphasis is placed on assessing the international economic situation caused by the pandemic, the restrictions adopted by the authorities to curb the spread of coronavirus and the actions of financial reporting compilers in terms of reflecting adjusting and non-adjusting events after the reporting period and assuming going concern. As a result of the study the world economic situation and the negative risks and factors that the financial reporting compilers should pay particular attention during the presentation and disclosure of information are examined